An epidemiological study on the prevalence and predictors for geriatric sarcopenia from a public hospital of Ooty, India - Rinta Elizabeth Reji, Surag B. Nair, Kannappan Subbaiah, David Sharon Cynthia, Sabitha Panchagiri, Sivasankaran Ponnusankar, Hunsur Nagendra Vishwas (Journal of Applied Pharmaceutical Science, 2023)
The study aimed at reporting the prevalence and predictors for sarcopenia in the elderly visiting a public hospital. The present study recruited patients aged >60 visiting the medicine department of Government Medical College Hospital, Ooty. Strength, assistance in walking, rise from a chair, climb stairs, and falls questionnaire (SARC-F), Ishii score, sociodemographic data, and nutritional status were collected to analyze the possible association with sarcopenia. Data were subjected to bivariate analysis and subsequent multivariate logistic regression. About 325 elderly were recruited for the study. Most of them belonged to low socioeconomic status (85.54%) and were found to be either malnourished (34.15%) at risk of malnourishment (51.08%). The prevalence of sarcopenia was 47.69% and 63.08% as per SARC-F and Ishii scoring systems, respectively. The logistic regression model identified smoking (OR-3.585, p = 0.014), unsatisfied sleep (OR-4.242, p < 0.001), nutrition [malnourishment (OR-17.237, p < 0.001), risk of malnourishment (OR-5.026, p = 0.002)] and lower socioeconomic status (OR-4.210, p = 0.033) to be predictors for Sarcopenia according to SARC-F whereas for Ishii Scoring, BMI [
Keywords: Sarcopenia, India, elderly, SARC-F, public health